ANALISIS KEPEMIMPINAN TRANSFORMASIONAL, DISIPLIN, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL - Isman Kadar Kadar (MAGMA : JURNAL MAGISTER MANAJEMEN, 2015)
This study aimed to analyze the relationship between Transformational Leadership, Discipline and Work Motivation to Performance Civil Servants. Samples in this study as many as 153 employees of a total population of 246 employees Satpol-PP Bogor City. The sampling technique used was simple random sample (Simple Random Sampling). Data were analyzed using regression analysis. The results show that: First, the closeness of the relationship between transformational leadership with employee performance obtained a correlation coefficient of 0.592 that is in the category of the relationship is. The magnitude of the coefficient of determination between transformational leadership on employee performance that is equal to 35.1%. Second, the closeness of the relationship between the Discipline Working with employee performance showed the correlation coefficient (r) of 0.614 which is in the category of strong relationships. The magnitude of the coefficient of determination between Discipline Working with employee performance amounted to 40.8%. Third, the closeness of the relationship between work motivation with employee performance correlation coefficient of 0.564 that is in the category of the relationship is. The magnitude of the coefficient of determination between work motivation with employee performance that is equal to 31.9%. Fourth, the closeness of the positive relationship between Transformational Leadership, Discipline and Work Motivation simultaneously with employee performance obtained a correlation coefficient of 0.599 which has the power of the closeness of the relationship was. The magnitude of the coefficient of determination between Transformational Leadership, Discipline and Work Motivation simultaneously with employee performance that is equal to 35.9%,Keywords: Transformational Leadership, Discipline, Work Motivation and Performance